THE INFLUENCE DER, TA, AND ROA ON PBV IN SHARIAH-COMPLIANT COMPANIES IN INDONESIA IN THE CONTEXT OF POST-COVID-19 ECONOMIC RECOVERY - Hadi, Kuncoro; Nuraini, Nuraini (Fakultas Pertanian Universitas Mataram, 2024)
This study analyzes the influence of Debt to Equity Ratio (DER), Total Assets (TA), and Return on Assets (ROA) on Price to Book Value (PBV) in Shariah-compliant companies listed on the Indonesia Stock Exchange during the 2020-2023 period. The background of this research is the critical need to understand the factors affecting PBV in the context of post-COVID-19 economic recovery. The study employs panel data regression analysis, which enables the identification of relationships between these financial variables and the market valuation of Shariah-compliant companies. The findings indicate that DER and TA have a significant negative impact on PBV, whereas ROA has a significant positive effect. These results underscore the importance of prudent management of leverage and asset structure in Shariah-compliant companies to mitigate risk perception among investors, while strong profitability can enhance corporate valuation. The novelty of this study lies in its focus on Shariah-compliant companies in the post-pandemic environment, providing insights for investors and policymakers in formulating more sustainable investment strategies.